Peningkatan Kompetensi Komunikasi Kerja Melalui English For Specific Purpose (ESP) Bagi Siswa Tata Busana SMK Negeri 3 Palangka Raya - Ratu Ayu Nurindraswari; Sabarun Sabarun (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service (PKM) aims to improve the English language competency of students of SMK Negeri 3 Palangka Raya specifically English For Specific Purpose (ESP). The increasingly global needs of the fashion and textile industry, both for export and import and interaction with foreign clients, require graduates to have English communication skills that are not only general, but also specific according to the terminology of design, production, and marketing of fashion products. The methods used are interactive training, and Role-Play simulations, and direct practical assistance with a focus on design presentations, negotiations with clients or suppliers, and technical terminology for sewing patterns in English. The results of the PKM show an average increase in specific vocabulary mastery of 25% as well as a significant increase in student self-confidence in using English for work scenarios, as well as a better understanding of professional terms in the field of Fashion Design. This activity is recommended to be continued as a regular school program to bridge the gap between the general English curriculum and the demands of actual work competencies in the fashion industry